Scientific frontiers in faecal microbiota transplantation: joint document of Asia-Pacific Association of Gastroenterology (APAGE) and Asia-Pacific Society for Digestive Endoscopy (APSDE). Issue 1 (14th October 2019) - Ng, Siew C; Kamm, Michael A; Yeoh, Yun Kit; Chan, Paul K S; Zuo, Tao; Tang, Whitney; Sood, Ajit; Andoh, Akira; Ohmiya, Naoki; Zhou, Yongjian; Ooi, Choon Jin; Mahachai, Varocha; et al.
Abstract : Objective: The underlying microbial basis, predictors of therapeutic outcome and active constituent(s) of faecal microbiota transplantation (FMT) mediating benefit remain unknown. An international panel of experts presented key elements that will shape forthcoming FMT research and practice. Design: Systematic search was performed, FMT literature was critically appraised and a 1-day round-table discussion was conducted to derive expert consensus on key issues in FMT research. Results: 16 experts convened and discussed five questions regarding (1) the role of donor and recipient microbial (bacteria, viruses, fungi) parameters in FMT; (2) methods to assess microbiota alterations; (3) concept of keystone species and microbial predictors of FMT, (4) influence of recipient profile and antibiotics pretreatment on FMT engraftment and maintenance and (5) new developments in FMT formulations and delivery. The panel considered that variable outcomes of FMT relate to compositional and functional differences in recipient's microbiota, and likely donor-associated and recipient-associated physiological and genetic factors. Taxonomic composition of donor intestinal microbiota may influence the efficacy of FMT in recurrent Clostridioides difficile infections and UC. FMT not only alters bacteria composition but also establishes trans-kingdom equilibrium between gut fungi, viruses and bacteria to promote the recovery of microbial homeostasis. FMT is not a one size fits all and studies are required to identify microbial components that have specific effects in patients with different diseases. Conclusion: FMT requires optimisation before their therapeutic promise can be evaluated for different diseases. This summary will guide future directions and priorities in advancement of the science and practice of FMT.